Pyrazolyl-s-triazine with indole motif as a novel of epidermal growth factor receptor/cyclin-dependent kinase 2 dual inhibitors - Shawish, Ihab; Nafie, Mohamed S.; Barakat, Assem; Aldalbahi, Ali; Al-Rasheed, Hessa H.; Ali, M.; Alshaer, Walhan; Al Zoubi, Mazhar; Al Ayoubi, Samha; De la Torre, Beatriz G.; Albericio, Fernando; El-Faham, Ayman (Frontiers in Chemistry, 2022)
A series of pyrazolyl-s-triazine compounds with an indole motif was designed, synthesized, and evaluated for anticancer activity targeting dual EGFR and CDK-2 inhibitors. The compounds were tested for cytotoxicity using the MTT assay. Compounds 3h, 3i, and 3j showed promising cytotoxic activity against two cancer cell lines, namely A549, MCF-7, and HDFs (non-cancerous human dermal fibroblasts). Compound 3j was the most active candidate against A549, with an IC50 of 2.32 ± 0.21 μM. Compounds 3h and 3i were found to be the most active hybrids against MCF-7 and HDFs, with an IC50 of 2.66 ± 0.26 μM and 3.78 ± 0.55 μM, respectively. Interestingly, 3i showed potent EGFR inhibition, with an IC50 of 34.1 nM compared to Erlotinib (IC50 = 67.3 nM). At 10 μM, this candidate caused 93.6% and 91.4% of EGFR and CDK-2 inhibition, respectively. Furthermore, 3i enhanced total lung cancer cell apoptosis 71.6-fold (43.7% compared to 0.61% for the control). Given the potent cytotoxicity exerted by 3i through apoptosis-mediated activity, this compound emerges as a promising target-oriented anticancer agent.